2021
DOI: 10.3390/antiox10060923
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Clot Formation under Oxidative Stress Conditions

Abstract: During coagulation, the soluble fibrinogen is converted into insoluble fibrin. Fibrinogen is a multifunctional plasma protein, which is essential for hemostasis. Various oxidative posttranslational modifications influence fibrinogen structure as well as interactions between various partners in the coagulation process. The aim was to examine the effects of oxidative stress conditions on fibrin clot formation in arterial atherothrombotic disorders. We studied the changes in in vitro fibrin network formation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…32 The rupture of coronary atherosclerotic plaques and the formation of thrombi result in a blood flow blockade in an infarct-related artery area and are closely associated with acute coronary syndrome. 33 Inflammation is crucial to the initiation and progression of this process as well as its poor consequences. 34 Additionally, innate immunity and adaptive immunity are essential for atherosclerotic plaque rupture.…”
Section: Discussionmentioning
confidence: 99%
“…32 The rupture of coronary atherosclerotic plaques and the formation of thrombi result in a blood flow blockade in an infarct-related artery area and are closely associated with acute coronary syndrome. 33 Inflammation is crucial to the initiation and progression of this process as well as its poor consequences. 34 Additionally, innate immunity and adaptive immunity are essential for atherosclerotic plaque rupture.…”
Section: Discussionmentioning
confidence: 99%
“…From these results, it can be inferred that there is a close relationship between fibrinogen-bound 3-nitrotyrosine and stroke-related thrombosis, but the underlying mechanism remains elusive. A recent study further analyzed the influence of oxidative stress on fibrinogen function and fibrin network formation in patients with acute ischemic stroke [ 17 ]. The authors demonstrated that acute ischemic stroke patients showed a higher level of malondialdehyde, a marker of oxidative stress in vivo .…”
Section: The Mechanism Of Oxidative Stress In Stroke-related Thrombosismentioning
confidence: 99%
“…Moreover, they found that the final optical density of clots was higher and the lysis time of clots was prolonged in acute ischemic stroke patients. Interestingly, the clots from these patients exhibited thicker fibers but lower fibers number in comparison with the control group [ 17 ]. Consistent with this finding, exposure of fibrinogen to oxidative stress such as H 2 O 2 and NO in vitro also led to a similar change in the clot structure [ 115 , 116 ].…”
Section: The Mechanism Of Oxidative Stress In Stroke-related Thrombosismentioning
confidence: 99%
See 2 more Smart Citations